Criminal Justice System in India, its objectives, components, drawbacks and Strategy for Reform : A Review - Gupta, Abhishek (Innovative Research Thoughts, 2018)
Criminal Justice refers to government agencies for the enforcement of the law, deciding crime and improving criminal conduct. The criminal justice system is essentially a means of social control: society considers some behaviors so dangerous and destructive that it either strictly controls their events or stops them altogether. It is the work of justice agencies to arrest these criminals by arresting and punishing criminals or by removing their future events. While society retains other forms of social control, such-as school, family, & church, they are designed to deal with legal, ethical, misbehavior. Simply the criminal justice system has the authority to control crime & punish criminals.